2004
DOI: 10.1007/s00441-004-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin expression is downregulated in a murine model of colitis and in patients with ulcerative colitis, Crohn’s disease and infectious colitis

Abstract: Colitis is associated with alterations in electrolyte and water transport. These changes give rise to some of the symptoms experienced by patients with colitis. Alterations in fluid flux may also contribute to increased susceptibility to mucosal injury. Recently, endogenous water channel proteins (aquaporins; AQPs), have been identified in colonic tissue. The expression of AQP4, AQP7 and AQP8 was examined, via reverse transcription/polymerase chain reaction, Western blotting and immunohistochemistry, in a muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 45 publications
5
81
2
3
Order By: Relevance
“…S1H). These genes are known to be down-regulated in human and mouse colitis (24). The data thus show that the Shp2 mutation in the intestine results in goblet cell deficits and colitis.…”
Section: Resultsmentioning
confidence: 61%
“…S1H). These genes are known to be down-regulated in human and mouse colitis (24). The data thus show that the Shp2 mutation in the intestine results in goblet cell deficits and colitis.…”
Section: Resultsmentioning
confidence: 61%
“…In humans, lower expression of AQP4 in colonic mucosa is correlated with the development of slow transit constipations (Wang et al 2010). Changes in expression levels of AQP4 were additionally observed in inflammatory diseases such as colitis (Hansen et al 2009), ulcerative colitis and Crohn's disease (Hardin et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…We observed that AQP1 deficiency reduces neutrophilic inflammation as well as cytokine release in silica-induced lung inflammation. Besides the respiratory tract, AQPs have been associated with inflammation in other organs (38,39). In a model of peritoneal dialysis, reduced accumulation of leukocytes was observed in mice genetically deficient in AQP1 (40).…”
Section: Discussionmentioning
confidence: 99%